(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
The paper describes the research work about limitations, complications, weaknesses, and success factors that can occur through applying LEAN – a quality management system - in Austrian companies. Applying a quantitative research approach, a detailed questionnaire about the innovation status of the subject matter was sent to 1367 companies. Two hundred twenty-two thoroughly answered questionnaires provided sufficient feedback to demonstrate the statistical significance of the results. The statistical description of the findings unveils the following elements: (1) LEAN methods, (2) LEAN principles, (3) LEAN thinking, together with (4) smart integration of Industry 4.0/5.0 enables enormous advantages in the pursuit of success of any corporation in the survey. However, the complexity of business processes, the limitations in strategic scope, and the weak implementation of LEAN systems hinder companies from unfolding the full potential of LEAN management. Primarily, over-optimized utilisation of the concept and the persistent resistance of employees against any change are explained in detail and enriched with anecdotal descriptions. The research results are explained with bar charts and tables to provide a clear and coherent presentation: LEAN processes are the prerequisites for any sustainable digitalisation efforts in the future.